Procedure related complications following implantation of cardiac resynchronization therapy (CRT) and implantable cardioverter-defibrillator (ICD) devices - Insights from the German DEVICE registry. (19th May 2022) - Kaiser, L; Hochadel, M; Senges, J; Kleemann, T; Szendey, I; Voss, F; Steinbeck, G; Leschke, M; Butter, C; Becker, R; Willems, S; Hakmi, S
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Stiftung Institut für Herzinfarktforschung Background: The number of patients receiving cardiac resynchronization therapy (CRT) and implantable cardioverter-defibrillator (ICD) devices has been increasing in the last decades. Both CRT and ICD play an essential role in modern heart failure therapy. However, the implantation procedure might be ensued by serious complications. Therefore, knowledge about the prevalence of complications and identification of risk factors are key to improve patient care. Methods: Between 2007-2014 the German DEVICE registry enrolled patients from 50 German centers undergoing ICD or CRT implantation. Patient characteristics, data on procedural outcome, adverse events and mortality during index hospitalization and follow-up at 1 year from discharge, were recorded. Patients who suffered from perioperative complications during or shortly after device implantation were identified for comparative analysis with patients without complications. Results: Out of 4170 patients enrolled, 119 (2.9%) suffered from procedure related complications. The proportion of female patients suffering from perioperative complications was higher with 29.4%, compared to 18.5% of female patients without complications (p=0.003). There were neither any differences in age (66.3±13.6 vs. 65.4±12.5 years; p=0.13), nor in cardiac or non-cardiac comorbidities and in the indications for device implantation between groups. There was a trend towards a higher rate of complications with procedures on pre-existing devices (24, 8 vs. 18.1%; p=0.064), than observed with de-novo implantations (75.2 vs. 81.9%; p=0.064). CRT implantations were more frequent among patients who suffered from complications (46.2 vs. 28.9%; p<0.001), compared to the group without complications, in which the proportion of ICD implantations was much more frequent (53.8 vs. 71.1%; p<0.001). The most frequent complication overall was pocket hematoma (55.1%), followed by pneumothorax (30.3%), pericardial effusion/tamponade (12.7%) and haemothorax (4.2%). The median hospital stay was significantly longer for patients with complications (7 [5; 11] vs. 3 [2; 5] days; p<0.001)). There was no difference in all-cause in-hospital mortality between respective groups. Median follow-up was 455 [398; 551] vs. 462 [391; 569] days (p=0.82) with no differences in all-cause mortality (6.5 vs. 6.9%; p=0.88), device-associated complications (12.6 vs. 8.5%; p=0.18) or rehospitalizations (37.9 vs. 32.2%; p=0.26) after 1-year follow-up. Conclusion: The overall procedure-related complication rate following CRT or ICD implantation is low (2.9%). Among patients with complications female gender and patients receiving CRT devices were more prevalent. Perioperative device complications neither seem to translate into increased in-hospital mortality, nor in increased rates of further device-associated complications, rehospitalizations or death after 1-year follow-up.